Students’ Perception of Using YouTube Application in The Context of English Language Learning - Fachrurrazy, Danny; Muhassin, Mohammad; Nawawi, Muhammad (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2025)
This study explores university students' perceptions of YouTube as an English language learning medium. With digital platforms increasingly complementing traditional education, YouTube offers a flexible, accessible repository of content that enhances listening, speaking, vocabulary, and grammar skills. Employing a qualitative descriptive approach, semi-structured interviews were conducted with five students from the English Language Education Study Program at UIN Raden Intan Lampung State Islamic University. The collected data were analyzed using the Miles and Huberman model, revealing that students value YouTube for its interactive content and the opportunity to learn at their own pace through trusted channels such as BBC Learning English and TED Talks. Respondents reported that YouTube effectively supplements their learning especially in authentic conversational contexts and exam preparation while also noting challenges including inconsistent content quality, distracting advertisements, and difficulties in finding material suitable to their proficiency level. The findings suggest that integrating YouTube with traditional classroom instruction may enhance overall language proficiency, highlighting the need for further research on optimizing digital media use in language education